Workplace-based competence measurement : developing innovative assessment systems for tomorrow's VET programmes - Achtenhagen, Frank [Verfasser]; Winther, Esther [Verfasser] (My University, 2014)
"As a consequence of the large-scale assessment studies (TIMMS; PISA) in compulsory schooling, attention is now being given to the modelling and measurement of competencies in initial vocational education and training. This new output-led perspective of teaching/training and learning/working processes demands new approaches to research. Using the concept of the curriculum-instruction-assessment triad this paper argues that competencies in the fields of business and commerce education can be determined and compared internationally via a large-scale assessment. Empirical results are presented that demonstrate the possibilities of running such an international study in VET." (Authors' abstract, BIBB-Doku)
Keywords: L 8 Diagnostik / Eignung; L 6.2.1 Standards/Gütekriterien; Berufsbildung; Kompetenzdiagnostik; Kompetenzfeststellung; Berufsbildungs-PISA; Kaufmännische Ausbildung